Becoming inclusive : a worthy pursuit in leadership - Fagan, Helen Abdali Soosan (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"To disrupt current polarization and tribalism, and meet the growing demands of globalization, organizations and communities must evolve. Such profound transformation begins with developing leaders who are prepared to create inclusion in boardrooms, classrooms, hospitals, communities, and beyond. Through the lens of her own story of immigrating from Iran to the United States and her experience leading diversity programs in health care and education, Dr. Helen Fagan presents a challenging discussion of the research along with a frank, intimate look at the very hard work leaders must do at an individual level to overcome personal obstacles to inclusion. Becoming Inclusive reveals the systemic problems of organizational bias and prejudice and shows university students, instructors, organizational and government leaders a path forward. This work seeks to fill the gap in the management, leadership and diversity field of work that focuses on the need to transform the mindsets of individual leaders from tribal to global, in order to address the big issues facing humanity"--